Kesulitan Siswa dalam Memecahkan Masalah Barisan dan Deret Aritmatika - Ayu Marida Silaban; Kerdid Simbolon; Jitu Halomoan Lumbantoruan (S&Co Publishing, 2022)
The purpose of this research is to analyze students' difficulties in problem-solving in arithmetic sequences and series. The subject of this research is a student at SMA HKBP Lintongnihuta. This research approach is descriptive quantitatively. The types of students' difficulties experienced were analyzed based on Polya's stages of problem-solving. The results of this research are three categories of students based on achievement scores, namely the low category with a percentage of 50%, the medium category with a percentage of 30%, and the high category with a percentage of 20%. There are 4 types of difficulties experienced by students, that is: (1) difficulty in understanding the problem with the number of students experiencing it as much as 28%, (2) students' difficulties in planning problem solving with the number of students experiencing it as much as 11%, (3) students' difficulties in carrying out the plan in problem-solving with the number of students experiencing it as much as 12%, and (4) difficulty in looking back at answers with the number of students experiencing it as much as 8%. The type of difficulty that most students experience is in understanding the problem.